Precipitation behavior of a new Cu-Ni-Co-Si-Fe-Mg alloy designed with low cobalt content - Liu-xin Qin; Tao Zhou; Xu Wang; Yan-bin Jiang; Feng Liu; Zhu Xiao; Qian Lei; Yan-lin Jia; Yi Luo; Zhou Li (Materials & Design, 2024)
A new Cu-1.5Ni-0.7Co-0.7Si-0.3Fe-0.1Mg alloy with low cobalt content was designed. Multi-stage thermo-mechanical treatment (MTT) was used to produce the high-performance alloy with hardness of 286 HV, yield strength of 858 MPa, tensile strength of 910 MPa and electrical conductivity of 45.4 % IACS. The addition of 0.3 wt% Fe element dissolved in (Ni,Co)2Si resulted in the formation of the orthorhombic δ-(Ni,Co,Fe)2Si. During MTT, the δ-(Ni,Co,Fe)2Si, (Ni,Co)2Si, β-Ni3Si, and Fe2Si precipitated successively near the deformation microstructure. Transmission electron microscope observations indicated that the δ-(Ni,Co,Fe)2Si precipitates showed disc-like and rod-like shapes at different orientations, respectively. A new resource-saving, high-strength and medium-conductivity Cu-Ni-Co-Si-Fe-Mg alloy was prepared by replacing an equal amount of Co element with 0.3 wt% Fe element, reducing the amount of scarce metal Co in the alloy.